Investigation and control of the ticking noise of the full floating piston pin. (April 2023) - Li, Zhibo; He, Xiping; Yang, Yi; Liu, Qiang
The focus of this work is to investigate the ticking noise produced by the vibro-impacts between piston pin and connecting rod small head bearing. Numerical calculation and experimental verification methods were adopted and a novel method to control this intermittent noise was proposed. The dynamic model of crankshaft connecting rod piston with full floating piston pin was established and the essence of piston pin ticking was analyzed. The occurrence time of the ticking corresponded to the crankshaft angle when the resultant force of piston pin passed through the 0 axis. At the moment of impact, the peak hydraulic pressure of lubricating oil was found to be proportional to the impact strength. In order to suppress this noise, the oil groove on the bearing was designed considering the minimum oil film. After adding the oil groove, the impact intensity was significantly reduced and the noise was even eliminated. The calculated results were in good agreement with the experimental tests, and the research of this work provided a reference for controlling the ticking noise of piston pin.